SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL STUDIES OF SCHIFF BASE DERIVED FROM 4-METHYL-o-PHENYLENEDIAMIE AND 2-HYDROXNAPTHALDEHYDE AND ITS METAL (II) COMPLEXES - Kabir, Abdullahi Muhammad; Aliyu, Habu Nuhu; Jabbi, Abubakar Muhammad; Isyaku, Suleiman (FUDMA JOURNAL OF SCIENCES, 2020)
Schiff base of 4-methyl-o-phenylenediamine and 2-hyroxy-1-napthaldehyde was synthesized and was used to prepare some metal (II) complex by refluxing with Metal (II) chloride ions. The ligand and its complexes were characterized by melting point and decomposition temperature, FTIR, solubility, magnetic susceptibility, conductivity measurement and elemental analysis. The IR spectral data revealed that, the  Schiff base coordinated to the respective metal(II) ion through the azomethine nitrogen and phenolic oxygen due to the shifting  of the azomethine band υ(C = N) from 591cm–1 to 1603 and 1581cm-1 in the spectra of the complexes. The band at 567 and 563cm-1 were due to υ(M–N), and 729-752cm–1 due to υ(M–O) and the infrared spectra of the metal(II) complexes showed strong bands 3443 and 3363cm–1 suggesting the presence of coordinated water in the metal complexes. Molar conductance values determined 9.17 and 10.04W–1cm2mol–1 showed that, the complexes were non-electrolytes. The ligand and its metal (II) complexes are not soluble in water and most organic solvents except DMF and DMSO. The melting point of the ligand and the decomposition temperatures of the metal (II) complexes were 243 and 224oC, which indicated their good thermal stability. The magnetic moment values of the metal (II) complexes obtained were 5.65 and 5.22BM for Mn(II) and Fe(II) complexes. This positive values indicated that they were paramagnetic. The elemental analysis suggested a metal to ligand ratio of 1:2. The antibacterial and antifungal test carried out on the ligand and its metal (II) complexes sowed moderate activity.